Recurrent Themes in Chichewa Verse in Malawian Newspapers (Nordic Journal of African Studies, 2003)
The paper discusses verse written in Chichewa, the national language of Malawi, that is published in Malawian newspapers, specifically the weeklies; the Weekend Nation and the Malawi News. The paper contends that the verse appearing in these newspapers are topical, essentially socio-political commentary that at the time of publication preoccupies the Malawi nation. Because the newspaper as a medium is populist the verse itself tends to be populist as well. This entails that the verse is largely ephemeral and its interest to a large extent lies not in its intrinsic quality but rather in the implications it may hold for the development of Chichewa poetry.